KONTROL DAN AUDIT WEBSITE COMPANY PROFILE PT. ADIPA KARYA – MEDAN - Suci Rahmadani; Suci Sundari; Beby Khilaw Handini; Elisa Priscilia Anasthasia Sitorus; Dwinando Sitompul (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2022)
The world of information technology (IT) has now become an inseparable part of human life, and its uses also vary, from entertainment functions to more complex functions such as machine learning (ML) and artificial intelligence (AI). The essence of its use is to obtain fast, accurate and accurate information. Using information technology PT. As a company engaged in the electricity industry, Adipa Karya has also taken advantage of this development in the form of a company profile website. project notes. However, the facts prove that its utilization is still not optimal, so it is still necessary to conduct research or audit on all aspects of the information presented. mission.